3D virtual histology of rodent and primate cochleae with multi-scale phase-contrast X-ray tomography - Jannis J. Schaeper; Christoph A. Kampshoff; Bettina J. Wolf; Lennart Roos; Susann Michanski; Torben Ruhwedel; Marina Eckermann; Alexander Meyer; Marcus Jeschke; Carolin Wichmann; Tobias Moser; Tim Salditt (Scientific Reports)
Abstract Multi-scale X-ray phase contrast tomography (XPCT) enables three-dimensional (3D), non-destructive imaging of intact small animal cochlea and apical cochlear turns. Here we report on post-mortem imaging of excised non-human primate and rodent cochleae at different $${\upmu }$$ -CT and nano-CT synchrotron instruments. We explore different sample embeddings, stainings and imaging regimes. Under optimized conditions of sample preparation, instrumentation, imaging protocol, and phase retrieval, high image quality and detail level can be achieved in 3D reconstructions. The showcased instrumentation and imaging protocols along with the reconstucted volumes can serve as benchmarks and reference for multi-scale microanatomy and 3D histology. The provided benchmarks and imaging protocols of this work cover a wide range of scales and are intended as augmented imaging tools for auditory research.